Exploring the Utility of Urinary Creatinine Adjustment for KIM-1, NGAL, and Cystatin C for the Assessment of Kidney Function: Insights from the C-KidnEES Cohort - T. D. K. S. C. Gunasekara; Chula Herath; P. Mangala C. S. De Silva; Nishad Jayasundara (MDPI AG, 2023)
Normalization of urinary biomarkers of kidney injury is a common practice in clinical and research settings to account for variations in urine concentration, and urinary creatinine is often used as a reference. However, to date, there is no consensus on the adjustment of urinary biomarkers with creatinine, and both absolute and creatinine-adjusted biomarker levels are adopted for making interpretations of kidney health. Hence, the present study aimed to investigate the associations of urinary creatinine with three widely used kidney injury biomarkers, KIM-1, NGAL, and cystatin C, to validate the applicability of urinary creatinine as a reference for normalization. A cross-sectional study was performed with 2100 students, 10-18 years of age in the Children's Kidney Environmental Exposure Study (C-KidnEES) cohort established in Sri Lanka. As identified in linear regression analyses, normalization of urinary KIM-1, NGAL, and Cys-C to urinary creatinine did not result in significant under-adjustment or over-adjustment to the absolute urinary concentrations, giving no specific rationale for creatinine adjustment. Hence, absolute urinary concentrations of the above biomarkers can be adopted for the characterization of subclinical kidney injury in adolescents in community studies where early morning urine sampling is practiced. However, for spot urine samples, consideration of both absolute and creatinine-adjusted biomarker levels would be a better approach.